2017
DOI: 10.1371/journal.pone.0188108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic and acute academic stress on lymphocyte subsets and monocyte function

Abstract: This study investigated the effects of a temporally confined naturalistic stressor (academic stress) on immune functions. Furthermore, moderating influences of a number of psychological variables were assessed. Five blood samples were obtained from 20 students during an observation period of 8 weeks, starting 4.5 weeks before an exam period up to 1 week following the last exam. The analysis of 45 immune parameters revealed several time-dependent changes attributable to examination stress. We observed a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 65 publications
2
25
0
3
Order By: Relevance
“…Increased NLR (24, 27) and mild anemia have been reported in patient populations as a result of chronic stress or chronic inflammation (28, 29). Also consistent with our findings, a stress-induced decrease in monocytes and T cells in humans has been reported (30). However, other studies have demonstrated elevated monocyte levels in the blood of chronically stressed humans and increased contribution of inflammatory cell populations from bone marrow resulting from chronic stress in mice (3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased NLR (24, 27) and mild anemia have been reported in patient populations as a result of chronic stress or chronic inflammation (28, 29). Also consistent with our findings, a stress-induced decrease in monocytes and T cells in humans has been reported (30). However, other studies have demonstrated elevated monocyte levels in the blood of chronically stressed humans and increased contribution of inflammatory cell populations from bone marrow resulting from chronic stress in mice (3).…”
Section: Discussionsupporting
confidence: 93%
“…While our study did not demonstrate these changes in the blood at the early (10-day) time point, it is possible that continued CUS would result in similar changes or that the observed reduction in circulating immune cells may be reflective of redistribution of these cells from the blood to the tissue. Thus, it is important to note that the immune impact of chronic stress can be highly time and context dependent and can vary with intensity and duration of the stressor, the strain or animal model employed, and the method and tissue type examined (30, 31) [reviewed in Ref. (23)].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we found a lower level of mature NK cells, which was previously demonstrated to correlate with high stress levels. Similar results were also observed in a previous study (Maydych et al, 2017[ 38 ]). The reason for the reduced amount of mature NK cells during stress is not clear so far, but our hypothesis is that mature immune cells migrate into lymphnodes instead of circulating in the blood.…”
Section: Discussionsupporting
confidence: 92%
“…After exercise, a balanced and simple carbohydrate diet, such as 30-60 g/h, has immunomodulatory effects as observed in athletes. These effects are decreased systemic IL-6 release neutrophils, monocytes, lymphocytes, less suppression of CD4 + and CD8 + T cells, which causes leukocyte distribution and immune responses such as neutrophil degranulation and oxidative stress, lymphocyte proliferation and functions (Maydych et al, 2017;Peake et al, 2017).…”
Section: Carbohydratementioning
confidence: 99%